The Effect of Company Size, Board of Directors Size, Profitability, Leverage Against Islamic Social Reporting on Sharia Commercial Banks in Indonesia - Dedy Suriadi (PT. Publikasiku Academic Solution, 2023)
This study aims to examine the effect of company size, board size, profitability, leverage on Islamic social reporting on Islamic commercial banks in Indonesia. The population in this study is all Sharia Commercial Banks in Indonesia as many as 14 Sharia Commercial Banks in the period 2016-2019. The sampling technique is a saturated sampling technique which is often called the census method. The data source in this study used secondary data. The analysis method used is multiple linear regression analysis. The results of this study show that company size, board of directors size, profitability, and leverage together affect Islamic Social Reporting (ISR) at Sharia Commercial Banks in 2016-2019. Furthermore, the size of the company negatively affects ISR. The size of the board of directors positively affects ISR. Profitability negatively affects ISR, and leverage negatively affects ISR in Sharia Commercial Banks in 2016-2019.